The books of the Bibles in early Christianity - Jordan Scheetz (HTS Teologiese Studies/Theological Studies, 2012)
A resurgence in the interest in other early Christian literature has brought the issue of the Christian biblical canon(s) to the forefront. Questions in relation to what the literature was, which literature was authoritative, and when did it become authoritative, have all been reopened both on a popular and scholarly level. With this climate, a re-evaluation of primary source information in relation to the various lists was in order. The lists from Origen, Eusebius, the Muratorian Canon, Athanasius, and to a lesser extent Tertullian, were examined. The result was: a nuanced perspective that reflects a three level reading hierarchy that gave precedence to the unquestioned texts, allows for mediated expansion through the questioned texts, and calls for a complete correction of the rejected texts based on the first two levels. Further, although none of the lists are exactly alike, substantial agreement was established between these various lists spanning more than a 150 years. In contrast to Marcion, theological harmony did not appear to be the main consideration in these various lists.